Non-ossifying fibroma of bone and ipsilateral hypermelanic nevus. An example of the relationship between skeletal and pigment abnormalities. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
Non-ossifying fibroma of bone is a benign alteration, frequent in the first two decades of life, often asymptomatic, rarely responsible for pathologic fracture. It is usually diagnosed incidentally by a radiological examination that shows a localized osteolytic image. A treatment is not usually necessary because it tends to regress spontaneously with ossification and calcification. In case of multiple lesions associated with extraskeletal abnormalities, especially cafè-au-lait spots, you have to think about Jaffe-Campanacci syndrome. We present a case of non-ossifying fibroma of the tibia associated with extensive ipsilateral hypermelanic nevus and discuss the differential diagnosis from other conditions which associate hyperpigmentation and skeletal abnormalities.